Nanostructured zinc oxide films for UV photonic devices - Yu, Siu Fung. (2008)
This RGM 18/02 manpower matching grant was issued to recruit research staffs to support an A*STAR project 022-101-0033. This was because A*STAR had substantial cut on the manpower budget of the original proposal submitted to A*STAR. The main objective of this project is to demonstrate effective ultraviolet lasing from ZnO thin films obtained from filtered cathodic vacuum arc (FCVA) deposition technique. This is intended to show that our FCVA technique is capable to fabricate ultraviolet (UV) ZnO photonic devices. In this project, we have demonstrated high-temperature UV random lasing action in ZnO epilayers. The characteristic temperature of the ZnO epilayers was derived to be 127 K in temperature range from 300 to 570 K. The cavity length of the random lasers as a function of temperature was determined by Fourier transform spectroscopy. The cavity length decreased with an increase in temperature from ~8 μm at 300K to ~3 μm at 570 K. The optical gain of the ZnO epilayers at high temperature can be attributed to a self-compensation mechanism in the cavity length. Furthermore, the formation characteristics of closed-loop random cavities inside highly disordered ZnO films with and without rib waveguide structure are investigated. The size dependence of the random cavities inside the random media on temperature and pump intensity profile is studied by applying Fourier transform to the corresponding lasing spectra. Simple rate equation analysis has revealed that the formation of the random cavities depends mainly on the profile of the optical gain, which is a function of the pump intensity profile and carrier diffusion length of the random media. ATTENTION: The Singapore Copyright Act applies to the use of this document. Nanyang Technological University Library 3 We have also demonstrated visible and ultraviolet random laser action simultaneously from highly disordered ZnO polycrystalline thin films under optical excitation. It is found that the realization of ZnO grain boundaries by thermal annealing can provide sufficient optical gain (i.e., related to deep-defect-level radiative recombination) and coherent feedback to achieve random laser action at visible wavelength. Furthermore, the co-existence of visible and ultraviolet random lasing inside the highly disordered ZnO films is due to the size difference of the random cavities at different wavelength. In conclusion, it is shown that ZnO thin films with nano-grain fabricated from FCVA technique can be used to realize high-temperature UV lasing sources.